Derivatives usage by non-financial firms in emerging markets: the Peruvian case - Martín, Miguel Angel (2009)
Financial derivatives markets have reached a remarkable development in recent years but this pattern has not attained the same strength in developing countries. In consequence an important question arises: what is the development degree of financial derivatives markets in emerging countries and which variables influence the use of derivatives in the top companies? To analyze this topic Peru has been chosen as a reference and the Non-Financial Firms as well. In order to enhance objectivity an empirical study has been conducted through a structured survey directed to chief financial managers of companies classified among the TOP 1000 in the country. This information was collected in order to explain the effect of the determinants that influence the development of financial derivatives in Peru. The results show that the use of derivatives in Peru is low and the relevant factors affecting its development are the degree of training in derivatives and the market regulation. This outcome suggests that there should be patterns of behaviour for market agents and government entities to promote the use of derivatives as well as provide information for future research that might contribute to establish the most adequate mechanisms for market-development purposes.